Eimeria maxima Rhomboid-like Protein 5 Provided Partial Protection against Homologous Challenge in Forms of Recombinant Protein and DNA Plasmid in Chickens - Di Tian; Xiaoqian Liu; Xiangrui Li; Lixin Xu; Ruofeng Yan; Xiaokai Song (Vaccines, 2021)
Eimeria maxima (E. maxima) is one of the most prevalent species that causes chicken coccidiosis on chicken farms. During apicomplexan protozoa invasion, rhomboid-like proteins (ROMs) cleave microneme proteins (MICs), allowing the parasites to fully enter the host cells, which suggests that ROMs have the potential to be candidate antigens for the development of subunit or DNA vaccines against coccidiosis. In this study, a recombinant protein of E. maxima ROM5 (rEmROM5) was expressed and purified and was used as a subunit vaccine. The eukaryotic expression plasmid of pVAX–EmROM5 was constructed and was used as a DNA vaccine. Chickens who were two weeks old were vaccinated with the rEmROM5 and pVAX–EmROM5 vaccines twice, with a one-week interval separating the vaccination periods. The transcription and expression of pVAX–EmROM5 in the injected sites were detected through reverse transcription PCR (RT-PCR) and Western blot (WB) assays. The cellular and humoral immune responses that were induced by EmROM5 were determined by detecting the proportion of CD4+ and CD8+ T lymphocytes, the cytokine levels, and the serum antibody levels. Finally, vaccination-challenge trials were conducted to evaluate the protective efficacy of EmROM5 in forms of the recombinant protein (rEmROM5) and in the DNA plasmid (pVAX–EmROM5) separately. The results showed that rEmROM5 was about 53.64 kDa, which was well purified and recognized by the His-Tag Mouse Monoclonal antibody and the chicken serum against E. maxima separately. After vaccination, pVAX–EmROM5 was successfully transcribed and expressed in the injected sites of the chickens. Vaccination with rEmROM5 or pVAX–EmROM5 significantly promoted the proportion of CD4+/CD3+ and CD8+/CD3+ T lymphocytes, the mRNA levels of the cytokines IFN-γ, IL-2, IL-4, IL-17, TNF SF15, and IL-10, and specific IgG antibody levels compared to the control groups. The immunization also significantly reduced the weight loss, oocyst production, and intestinal lesions that are caused by E. maxima infection. The anticoccidial index (ACI)s of the vaccinated groups were beyond 160, showing moderate protection against E. maxima infection. In summary, EmROM5 was able to induce a robust immune response and effective protection against E. maxima in chickens in the form of both a recombinant protein and DNA plasmid. Hence, EmROM5 could be used as a candidate antigen for DNA vaccines and subunit vaccines against avian coccidiosis.